2005
DOI: 10.1002/prot.20444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of domains and domain interface residues in multidomain proteins from graph spectral method

Abstract: We present a novel method for the identification of structural domains and domain interface residues in proteins by graph spectral method. This method converts the three-dimensional structure of the protein into a graph by using atomic coordinates from the PDB file. Domain definitions are obtained by constructing either a protein backbone graph or a protein side-chain graph. The graph is constructed based on the interactions between amino acid residues in the three-dimensional structure of the proteins. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Domain identification by means of network approaches has been reported by Vishveshwara's group (Sistla and Vishveshwara, 2005). The group originally developed the method to identify backbone clusters, in which, edges can be defined in two ways, either based on C atom contacts (Method A), or taking side-chain interactions into consideration (Method C).…”
Section: Protein Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Domain identification by means of network approaches has been reported by Vishveshwara's group (Sistla and Vishveshwara, 2005). The group originally developed the method to identify backbone clusters, in which, edges can be defined in two ways, either based on C atom contacts (Method A), or taking side-chain interactions into consideration (Method C).…”
Section: Protein Domainmentioning
confidence: 99%
“…The clusters were identified by examining eigenvectors and eigenvalues, and the latter were obtained from the diagonalization of the network matrix. A domain within a protein was defined as a network community within which intensive interactions exist, and was identified using this method (Sistla and Vishveshwara, 2005). This method yields both domain definitions and interface residues in a single numeric computation.…”
Section: Protein Domainmentioning
confidence: 99%
“…A graph is a mathematical structure, which can be defined as a collection of vertices or nodes and a collection of edges that connect pairs of vertices. In particular, cliques and communities detection algorithms have been used in varied biological fields, for instance, in protein interaction predictions, protein domain detection [2], protein structural alignment, protein structural and dynamics studies and even in detection of RNA secondary structure motifs [3,4,5,6,7]. However, there are no available reports on successful application of graph theoretic algorithms for analyzing RNA dynamics and studying the correlated motions of the RNA.…”
Section: Introductionmentioning
confidence: 98%
“…The constructed representations were called protein structure graphs. Sistla et al (2005) converted the three-dimensional structure defined by the atomic coordinates of proteins into a graph and presented a method for the identification of structural domains of proteins. Jha et al (2009) showed how topological parameters derived from protein structures can be used for the sequence design for a given set of structures.…”
Section: Introductionmentioning
confidence: 99%